Multiple criteria decision‐making in healthcare and pharmaceutical supply chain management: A state‐of‐the‐art review and implications for future research - Laganà, Iside Rita; Colapinto, Cinzia (Journal of multi-criteria decision analysis, 2022)
Decisions in supply chain management (SCM) are subject to numerous conflicting criteria and multiple objectives. For such decisions, multiple criteria decision making (MCDM) methods are definitely appropriate. The implementation of the healthcare supply chain (HSC) is more complex to manage than any other supply chains, as it involves human life, causing conflicts of interest and hindering the final decision. Previous researchers suggested different SC models for healthcare products such as drugs, vaccines, and other medical equipment. This article provides an overview of published articles in the application of MCDM methods in HSCM at the strategic, tactical, and operational levels. We studied and categorized 139 articles published in 2006–2021, providing academic researchers, practitioners, and governments with insights into the application of different MCDM methods. The review allows us to establish guidelines for the selection of appropriate methods for HSC management and provide support to the management of issues in the healthcare and pharmaceutical sector.